2017
DOI: 10.1177/1753944716687517
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in peripheral artery disease

Abstract: Peripheral artery disease (PAD) has been associated with severe morbidity and mortality worldwide, affecting the quality of life for millions of patients. Acute thrombosis has been identified as a major complication of PAD, with proper management including both open as well as endovascular techniques. Thrombolysis has emerged as a reasonable option in the last decades to treat such patients although data produced by randomized trials have been limited. This review aims to present major aspects of thrombolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…19,35–37 Transplantation often results in DGF in these kidneys, 2,6–14,35,36 although a study from the Mayo Clinic, despite a significant difference in vascular resistance and arterial flow at evaluation, no significant difference in DGF was observed, although the control material had 39% and the study group had 49% DGF, that is, higher levels than more commonly reported. 37 Based on these and other studies in experimental animals and humans 21,38–40 as well as our early investigational studies, we selected a combination of Lys-plasminogen and tPA for perfusion and reconditioning of uDCD kidneys. Control uDCD kidneys not treated with Lys-plasminogen frequently appeared dark during perfusion, and sometimes with large black confluent areas suggesting necrosis during and after perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…19,35–37 Transplantation often results in DGF in these kidneys, 2,6–14,35,36 although a study from the Mayo Clinic, despite a significant difference in vascular resistance and arterial flow at evaluation, no significant difference in DGF was observed, although the control material had 39% and the study group had 49% DGF, that is, higher levels than more commonly reported. 37 Based on these and other studies in experimental animals and humans 21,38–40 as well as our early investigational studies, we selected a combination of Lys-plasminogen and tPA for perfusion and reconditioning of uDCD kidneys. Control uDCD kidneys not treated with Lys-plasminogen frequently appeared dark during perfusion, and sometimes with large black confluent areas suggesting necrosis during and after perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…One group received catheter-directed thrombolysis combined with percutaneous aspiration and, the other, open thrombectomy. In the group with thrombolysis, the patients with graft thrombosis after bypass surgery had better outcomes than those who had thrombosis in vessels [8] . The group of patients who received thrombolysis and percutaneous aspiration had a lower recurrence rate and mortality rate than the group who received open thrombectomies.…”
Section: Discussionmentioning
confidence: 93%
“…13 Thrombolysis can be considered for embolic disease in ALI, Rutherford class I or class IIa. 14 However, the mechanism of aortic occlusion has trended toward thrombotic events, decreasing from 50% to 68% embolic in the 1990s 3,13,15 to 7% embolic, 17% indeterminate, and 76% thrombotic in 2013. 2 Improved anticoagulation for atrial fibrillation 16 has possibly decreased the incidence of embolic aortic occlusions.…”
Section: Discussionmentioning
confidence: 99%